2017
DOI: 10.1177/0733464817735396
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Individually Tailored, Internet-Mediated Physical Activity Intervention in Older Adults: A Randomized Controlled Trial

Abstract: Individually tailored, Internet-mediated PA interventions are an effective way to significantly increase PA in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 16 publications
(17 reference statements)
2
53
0
Order By: Relevance
“…Thirty-eight articles were eligible for a qualitative synthesis. After the extraction of data, 13 articles were not included in the meta-analysis because the risk of bias as rated by the PE-Dro score was high (n = 2) [33,34], the mean and standard deviation at T1 of both groups were not provided (n = 4) [35][36][37][38], the effect size or standard deviation were outlined (n = 3) [39][40][41], the outcome variables were measured by fewer than three studies (n = 3) [42][43][44], and the data were from a preliminary analysis, which duplicated data in another study reporting the final analysis (n = 1) [45]. In the end, 25 articles were included in the meta-analyses of different outcomes.…”
Section: Study Selectionmentioning
confidence: 99%
“…Thirty-eight articles were eligible for a qualitative synthesis. After the extraction of data, 13 articles were not included in the meta-analysis because the risk of bias as rated by the PE-Dro score was high (n = 2) [33,34], the mean and standard deviation at T1 of both groups were not provided (n = 4) [35][36][37][38], the effect size or standard deviation were outlined (n = 3) [39][40][41], the outcome variables were measured by fewer than three studies (n = 3) [42][43][44], and the data were from a preliminary analysis, which duplicated data in another study reporting the final analysis (n = 1) [45]. In the end, 25 articles were included in the meta-analyses of different outcomes.…”
Section: Study Selectionmentioning
confidence: 99%
“…Twelve different studies met our inclusion criteria [21][22][23][24][25][26][27][28][29][30][31][32] (Table 1 for details and Fig. 1 for a flowchart of the search).…”
Section: Ehealth Interventions For Promoting Physical Activitymentioning
confidence: 99%
“…Sample sizes of studies varied from 40 [28] to 263 [21], with eight out of twelve studies including < 100 participants. The ICT modalities that were used by studies to deliver the interventions differed considerably, and four studies compared multiple interventions with one control condition [23,24,29,30]. The study by Thompson and colleagues simply compared wearing a smartwatch accelerometer, which provided feedback on PA, to a control condition [31], whereas the other studies evaluated more extensive eHealth solutions for changing PA behaviour.…”
Section: Ehealth Interventions For Promoting Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Tailored messages are thought to facilitate changes in several behaviors by providing personally relevant information and feedback [11]. Meta-analyses and narrative reviews have concluded that tailored messages are more effective than non-tailored ones in changing health behavior in multiple domains [13][14][15][16][17][18][19][20], including medication adherence [21], physical activity [22], and diet [23,24], all key aspects for the management of cardiovascular diseases. To date, little is known about the efficacy and the long-term outcomes of tailored versus non-tailored communication interventions: a large majority of studies on tailored interventions focused on short-term effects of tailored messages while few studies investigated long-term effects (most of them analyzed results up to six months after the intervention).…”
Section: Introductionmentioning
confidence: 99%